PERBANDINGAN METODE CENTROID DAN WARD DALAM PENGELOMPOKKAN TINGKAT PENYELESAIAN PENDIDIKAN DI INDONESIA - Rindang Ndaru Puspita (LPPM Universitas Bina Bangsa, 2022)
Education is foundation in building the nation and state, besides that education is a right for all citizens. Educational achievements in Indonesia can be seen from the achievement of educational graduation rates for all levels of education from elementary to high school. The government needs to pay more attention to education in Indonesia, so there needs to be a grouping of provinces according to similar characteristics, so that the government can focus more on preparing programs and activities to improve the quality of education. The right method for grouping provinces is the best method from the results of cluster analysis by comparing the centroid and ward methods as seen from the value of the cophenetic correlation coefficient. Based on the research, the best method was obtained, namely the centroid method with cluster profiling: cluster 1 is a cluster with a moderate level of completion of education consisting of 31 provinces, cluster 2 with a level of completion of higher education consists of 2 provinces, and cluster 3 with a low level of completion of education consists of 1 province